Comparison of the Legal Conditions of the State and the Division of Powers in the Constitution of Indonesia and Egypt - Marianus Tefi; Tunggul Anshari, S.N; Riana Susmayanti (Cita Konsultindo Research Center, 2023)
As a based on law state, Indonesia is demanded to be able to construct justice for citizens, through legal regulation. The constitution as the highest legal regulation contains basic norms that guarantee the rights of citizens, determine and divide state institutions’ structures, and limits their duties. The Indonesian constitution, which has been amended four times, can be said to be imperfect. By comparing the state's legal requirements and the pattern of distribution of power in the Egyptian Constitution, Indonesia, and Egypt have similarities in pattern for the formation of a state, which begins with the birth of a nation that lives in a certain territory, so that they have the political awareness be on one’s own and have a common will in forming their respective government systems. Meanwhile, the difference lies in the pattern of distribution of power and check and balance practices, where the power given by the constitution to the President of Egypt is greater than the others. In addition, it is also necessary to recognize the forms of application of the theory of social contract and the theory of consent of governed in both constitutions.